2013
DOI: 10.1007/s12098-013-1088-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Spectrum, Cytogenetic Analysis and Thyroid Profile of 418 Children with Down Syndrome from South India: A Cross-sectional Study

Abstract: The prevalence of congenital heart disease in children with Down syndrome in Kerala is the highest reported (63.4 %). Ventricular septal defect is the most common heart disease in the present study. The results highlight the changing attitudes of families towards the surgical correction of congenital heart disease in children with Down syndrome. Prevalence of hypothyroidism in Down syndrome in Kerala is 13.6 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Direct contact with the authors of the remaining 31 articles made it possible to include another eight studies [12,13,20,[26][27][28][29][30], totalizing 12 articles for analysis. In total, 20,465 patients with DS (11,165 male and 9300 female) were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Direct contact with the authors of the remaining 31 articles made it possible to include another eight studies [12,13,20,[26][27][28][29][30], totalizing 12 articles for analysis. In total, 20,465 patients with DS (11,165 male and 9300 female) were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that when characterising the profiles and types of CHD in DS, the dominant lesions observed are variable according to the different geographical areas around the world 7,8. Hence, for a given country, to know the profile and characteristics of CHD in DS is of great importance, first to improve survival by timely treatment of cardiac anomalies,10 and second to apply appropriate preventative measures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the profile and type of these CHDs are variable according to the different geographical areas around the world 7,8. Recent studies in Norway also suggest a seasonal variation in the occurrence of DS and birth defects, and provide indirect evidence of the causal role of environmental factors,since genetic factors do not exhibit seasonality 9.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of hypothyroidism in children and adults with Down syndrome has been reported to be as high as 4% to 18%. [254][255][256] The incidence increases over time and may relate to inadequate thyroid tissue or the increased incidence of autoimmunity in Down syndrome. 257 Adults with TOF and syndromic features have an elevated prev- …”
Section: Prevalence and Pathogenesismentioning
confidence: 99%